(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
يعدّ هذا العمل استمراراً لدراسة أطياف تألق الأشعة السينية (XRL) X – ray luminescence لأكسيد التوتياء النقي والمشوب بعناصر مختلفة في الأفلام الرقيقة والبلورات والمساحيق المحضرة بطرائق تقنية متطورة. فقد قمنا بدراسة أطياف التألق ضمن المجال (200-700)nm لأفلام رقيقة من أكسيد التوتياء النقية والمشوبة بشوارد من الألمنيوم بتراكيز وزنية مختلفة %Wt (5,10,15,20) , والمحضّرة بطريقة البخّ الحراري , وهي تقنية بسيطة وذات كلفة منخفضة نسبياً. أظهرت الدراسة قمماً طيفية تألقية عند الأطوال الموجية (335,410,521)nm بزمن تألق مميز وجديد t=20 ns، كما تم تحليل التغيّر في الشدات التألقية في الأطوال الموجية الناتجة من اختلاف التراكيز في الإشابة للأفلام الرقيقة ومقارنتها بالفيلم النقي. للأفلام الرقيقة تطبيقات علمية واسعة في المجال الطبي وخاصة الليزر وفي العدادات الومضانية وفي الخلايا الشمسية. The work could be considered as a continuous study of (XRL) X – ray luminescence - spectra of pure, and mixed Zno different AL ions, In these films and other crystals powders prepared by new developed te chnology. We studied the pure and ZnO thin films. mixed with an AL - ions in the fielol (200-700)nm ,at different weig hrs (5,10,15,20)wt% prepared by thermal evaporation. This way is cheep and a simple technology. Our study showed different spectra peaks at the wavelengths(335,410,521)nm anol (t=20ns)produced, at different peaks intensities of the prepared thin films, compared with those jure and mixeol ZnO ones, spray pyrolysis. Thin films technology, have many wide scientific application, in the medical field, Lazer technology, Luminscence counters, and at the solar cells fields.